Microporosity mediated proliferation of preosteoblast cells on 3D printed bone scaffolds. Issue 10 (6th May 2021) - Li, Jian; Chong, Yi Ting; Teng, Choon Peng; Liu, Jinyan; Wang, FuKe
Abstract: Microporous structure plays a significant role in bone tissue engineering, to influence inductive bone formation and elevate bone ingrowth inside microporous scaffolds. We hereby fabricated microporous scaffolds by 3D printing with mixture of porogens and photopolymerizing resin. Our method can tune the microporosity of scaffolds from 0% to 36% by varying the porogen concentration in the inks from zero to 60 vol%. The microporosity and microspore size of scaffolds can affect in vitro expansion of preosteoblast cells. We evaluated the attachment, spreading and proliferation of MC3T3‐E1 mouse preosteoblast cells on the printed porous scaffolds. Our studies revealed that preosteoblast cells' in vitro adhesion and proliferation were significantly mediated by the printed scaffolds. Cells proliferation on scaffolds with 20%–30% microporosity showed much higher rate than on other scaffolds. In this microporosity range, scaffolds also showed much better cell spreading and morphologies. At a low level of microporosity (< 7%), the cell proliferation rate was even lower than the solid scaffolds, which indicates that the microporous structure is "toxic" for cells at low microporosity range. A higher microporosity (> 35%) led to very poor cell attachment and is unfavorable for the proliferation of MC3T3‐E1 cells. Furthermore, the printed dual macro‐/micro‐porous scaffolds showed higher proliferation rate of MC3T3‐E1 cells as compared to mono‐pore sized scaffolds, either the macro‐porous or microporous structure. Abstract : Microporous structure for bone tissue engineering were manufactured by combination of 3D printing and porogen technique. In vitro study revealed a favorable microporosity range of the 3D printed scaffold for the adhesion and proliferation of preosteoblast Cells.